Value of sprinkling feedlot cattle during heat - Ames, D.R.; Willms, C. (Kansas State University. Agricultural Experiment Station, 2011)
Four lots of growing-finishing cattle were sprinkled when dry bulb temperature exceeded 80 F the summer of 1976 and compared with lots not sprinkled. Sprinkled lots gained significantly (P<.01) more (1.20 kg per day compared with 1.04) (2.64 vs. 2.29 lbs.) than controls. Sprinkling also improved feed efficiency (F/G).
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Sprinkling cattle; Feed efficiency; Gain